Just Diversion: Designing Eviction Mediation to Address Incentives and Inequities - Deanna Pantín Parrish (Washington University Journal of Law and Policy, 2022)
Mediation is a widely used approach to eviction diversion: over 65% of court-adjacent programs aimed at keeping tenants housed employ mediation at some stage. Many mediation programs that facilitate landlord-tenant disputes have their roots in foreclosure mediation programs that were used during The Great Recession. However, federal intervention during the mortgage foreclosure crisis incentivized parties, especially Plaintiffs, to participate in mediation, thus helping to level power asymmetries at-the-table. Eviction mediation programs do not benefit from any equivalent federally-set incentives schemes. Absent these levers or other policies addressing the root causes of housing instability, eviction mediation programs must bear the weight of many broken systems through thoughtful process design. Using a dispute system design (DSD) approach, this Article suggests options for how eviction mediation programs can “deliver justice.” Programs should be tailored to increase incentives for landlords, lower stakes for tenants, and calibrate power inequities between the parties. Designing eviction mediation programs with these considerations in mind not only helps address housing instability, it safeguards mediation and mediators from miscarrying justice.
Keywords: Eviction Mediation; Diversion; Dispute System Design (DSD)